Computing the Order, Conjugacy Classes and Character Table of the Full Non-Rigid Group of Cyclopropane Chemical Compound Using Wreath Product - Ben O. Johnson; Auta T. Jonathan (Journal of Current Research and Studies, 2026)
The full non-rigid molecules group (f-NRG) theory is seen to be used advantageously to study the internal dynamics of such molecules. In this paper, we determine the order of Cyclopropane and its conjugacy classes. We used computational method to compute the group and its character table and considered the point group of the compound which turned out to be isomorphic to the Wreath Products C3wrC2, where Cn denotes a cyclic group of order n. We found Cyclopropane to have order 18 and 9 conjugacy classes.